2015
DOI: 10.1007/s00345-015-1584-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profile of urothelial carcinoma of the upper urinary tract: are pelvicalyceal and ureteral tumors different?

Abstract: The prospective assessment of selected cell cycle and proliferative markers suggests no molecular difference between UTUC of the pelvicalyceal system and that of the ureter. Our study is limited by its size and definition of location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In our opinion, urothelial carcinoma should be regarded as a panurothelial disease. It was shown that the biological profiles are similar regardless of the tumour location (bladder, ureter, and renal pelvis) [25, 26]. Our results confirm this assumption to the extent that 83% of UTUC cases had high-risk BC, suggesting a relationship with tumour biology.…”
Section: Discussionsupporting
confidence: 84%
“…In our opinion, urothelial carcinoma should be regarded as a panurothelial disease. It was shown that the biological profiles are similar regardless of the tumour location (bladder, ureter, and renal pelvis) [25, 26]. Our results confirm this assumption to the extent that 83% of UTUC cases had high-risk BC, suggesting a relationship with tumour biology.…”
Section: Discussionsupporting
confidence: 84%
“…In a meta-analysis which included 17 studies with 12,094 patients, Wu et al demonstrated that ureteral tumors exhibited worse CSS and recurrence-free survival than renal pelvic tumors based on adjusted HRs; however, no such results were noticed in subgroup analysis of pT3/4 and pN1 tumors, though the authors observed significant heterogeneity among reported articles [ 4 ]. The only corresponding study that additionally included molecular work was published in 2013, in which Krabbe et al found no difference in the expression of p21, p27, p53, cyclin E, and Ki-67 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since both ureteral tumors and renal pelvic tumors originate from the urothelium, they have been traditionally classified as a single entity (UTUC) and managed in a relatively similar fashion, barring nephron-sparing approaches for more distally located tumors. In recent years there have been studies focusing on the impact of tumor location on prognosis [ 4 7 ], though evidence concerning clinical, pathological and genetic differences between renal pelvic and ureteral tumors remains scarce [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…131 p21 and p27 are tumor suppressor genes that have been studied in UTUC with mixed results. 132, 133 No correlation has been found between p21 expression and clinicopathologic variables, while p27 loss has been seen in up to 12% of cases and up to 33% of invasive tumors, and has been associated with a shorter overall survival. 132,134 However, others have found p27 status to have no prognostic value.…”
Section: Genetics and Molecular Pathwaysmentioning
confidence: 99%